Oil Palm Fibre Waste to Biogas Electricity Production Framework for Mill Operation - Husna Zakaria, Izatul; Jafni Azhan Ibrahim, Jafni; Aziz Othman, Abdul (International Journal of Engineering and Technology, 2018)
One of issue regarding of renewable energy supply chain is source sustainability and reliability to ensure continuous production. The aim of this paper is to suggest the oil palm fibre waste to biogas electricity production framework: mill operation perspective that suit to be practices based on evaluation of current practise of oil palm solid waste and Malaysia’s palm oil industry. The framework is based on palm oil mill operation to utilise annually solid waste generate as biomass source for stable biogas electricity production. This conceptual paper is the principal efforts that introduce the usage of storage system for biomass feed input to ensure sustainable stable electricity production from palm oil mill by manipulate their solid waste production. Prospective researchers are put forward to conduct further research to enhance biogas production as alternative for waste treatment strategy.